Unemployment in Ukraine: an Analysis of the Dynamics, Gender, Age Structure and Causes of Unemployment - CHERVONA, S. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2020)
The article examines the dynamics of the number of registered unemployed and unemployed in the definition of the International Labor Organization (ILO), as well as the levels of these indicators. It is determined that compared to 2010, the largest increase in the number of registered unemployed could be observed in 2011. The most significant decrease in the studied indicator during the entire research period, both compared to 2010 and the previous year, was in 2017. In 2018–2019, the number of registered unemployed continued to decline. The increase in the registered unemployment rate compared to 2010 was in 2011, 2013–2016, and a significant increase in the level of the studied indicator was recorded in 2015. The decrease in the studied indicator was recorded in 2012 compared to 2011, as well as in the last four years of the research period. The unemployment rates by the ILO methodology are most informative figures on the unemployment in Ukraine. The number of unemployed in 2010–2019 did not have a clear trend and depended on the socio-economic situation in Ukraine: compared to previous periods, the indicator decreased in 2011–2013, and in 2014 increased rapidly, due to the difficult socio-political situation in the country, which had adverse effects for the economic situation; in 2015, the average number of unemployed decreased both compared to the previous year and to 2010. However, in 2016–2017, the studied indicator began to grow gradually, but did not reach the level of 2010, and decreased in 2018 and 2019 both compared to the previous period and to 2010. Analysis of the intensity of the dynamics of the unemployment rate of the population aged 15–70 years by the ILO methodology showed that throughout the ten-year research period this indicator in Ukraine decreased in 2011–2013 and increased in 2014–2018 compared to 2010, and in 2019 it decreased to the level of 2010. The sex-age structure of the unemployed is analyzed, its features are revealed and the generalized age characteristics of the unemployed are determined. In contrast to the registered unemployment, which indicates the predominance of women among the unemployed, a sample survey allows to suggest that Ukraine is characterized by “male” unemployment. Among the unemployed, the largest share was accounted by young people aged 15–34. The highest unemployment rate among young people aged 15 to 24 was due to the fact that without proper education and professional experience, young people were not able to compete on equal terms on the labor market. The average age of the unemployed in Ukraine in 2019 compared to 2010 increased by four years, including almost four years for men and five years for women. Because this indicator cannot be used as a generalization due to the heterogeneity of the population, as evidenced by the indicators of variation, mode and median, which are the structural averages, are the most suitable for the generalization of the characteristics of the unemployed by age. The structure of the unemployed by cause of unemployment was studied, with assessing the structural change. It is established that during the studied period in Ukraine this structure was changed significantly, as evidenced by the root mean square coefficient of structural change.